Observation of ψ(3686) → Ξ − K S 0 Ω ¯ + $$ Ξ^{-}{K}_S^0{\overline{\varOmega}}^{+} $$ + c.c. - The BESIII collaboration; M. Ablikim; M. N. Achasov; P. Adlarson; X. C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; et al. (Journal of High Energy Physics, 2025)
Abstract Using a sample of (2.712 ± 0.014) × 109 ψ(3686) events collected with the BESIII detector at the electron positron collider BEPCII, the decay ψ(3686) → Ξ − K S 0 Ω ¯ + $$ Ξ^{-}{K}_S^0{\overline{\varOmega}}^{+} $$ + c.c. is observed for the first time, which has a significance of 5.9 standard deviations. The branching fraction of this decay is measured to be (2.91 ± 0.47 ± 0.33) × 10 −6, where the first and second uncertainties are statistical and systematic, respectively. The ratio between B ψ 3686 → Ξ − K S 0 Ω ¯ + + c . c $$ {\mathcal{B}}_{ψ (3686)→ {\varXi}^{-}{K}_S^0{\overline{\varOmega}}^{+}+c.c} $$ and B ψ 3686 → Ω − K + Ξ ¯ 0 + c . c $$ {\mathcal{B}}_{ψ (3686)→ {\varOmega}^{-}{K}^{+}{\overline{Ξ}}^0+c.c} $$ is determined to be 1.05 ± 0.23 ± 0.14, which deviates from the isospin symmetry conservation predicted value of 0.5 by 2.1σ.